Determinants of medical tourism considering a geographical model: a case study of Iran - Faridi Masouleh, Ali; Ziari , Keramatollah; Rezvani, Mohammadreza; Etaat, Javad; Khorasani, Mohammad Amin; Zabih-allah Torabi (Social Determinants of Health, 2022)
Background: Medical Tourism has received significant attention worldwide as the most remarkable phenomenon in the tourism industry. Medical Tourism was considered a medical tourist’s behavior concerning the push/pull factors and three fundamental flows to assess the BTD model (Birthplace-Transportation-Destination). The present study aimed to unearth determinable factors of medical tourism based on a geographical model named BTD in Iran. Methods: Firstly, with 301 respondents and 11 expert judges, after literature review, item building, and some assessments, the primary checklist leads to 49 items. Two next steps, some processes were common, including sample-to-item ratio (10.12, 10.24), the Cronbach’s alpha (over 0.81, 0.85-0.96), Bartlett’s Test (both were significant), and KMO (0.896, 0.915). Finally, EFA in the first study and PCA in the second study were assessed and reported. In the third study, to check multicollinearity, the VIF (1.809-2.917), AVE (0.50-0.55), and CR (0.59-0.68) were calculated. Then, AVE was compared with SIC. Ultimately, SEM was conducted that the 3-factor model, especially without the Mahalanobis distance, indicates better results. The study is developed in five cities called Khorasan, Tabriz, Tehran, Fars, and Isfahan. Results: Regardless of cost, other significant factors were recognized, including birthplace-related factors, transportation-related factors, and destination-related factors. Conclusion: As can be seen, the construction and the push/pull factors surveyed to assess the BTD model covering all main flows were well defined. Meaningful statistical relationships support the internal and external validity of the multidimensional construct. Therefore, present results are functional for interested sectors, and researchers must not disregard the market.